Is the Portuguese battery electric vehicles subsidy program encouraging the "right" consumers? - Granja, Guilherme Silva (2021)
To achieve carbon neutrality, the Portuguese government put in place a battery electric vehicle (BEV) subsidization program. By focusing on the non-additionality concept, we show that the percentage of BEVs buyers who would have bought them without the subsidy is smaller for low income households(more price sensitive)than for other households and corporations (27,43% vs 29,99%). Moreover, the welfare positive consequences for consumers are greater when targeting low income households, given that there are more marginal consumers who will be able to purchase a BEV. This results in lower CO2 emissions and increasing positive externalities. In summary, discriminating across different consumers is required for cost-effectiveness.